Ocean Enlightenment A Conversation with Edie Widder. - Burton, Howard (Ideas Roadshow Conversations Ser., 2020)
This book is based on an in-depth filmed conversation between Howard Burton and Edie Widder, Founder, CEO and Senior Scientist at Ocean Research & Conservation Association (ORCA). After an inspiring story about how Edie Widder became a seagoing marine biologist and deep-sea diver, this conversation covers topics such as bioluminescence which is a fascinating scientific phenomenon that provides us with a deeper understanding of fundamental biological processes and the development of new programs designed to equip a new generation with the tools they need to deal with the environmental devastati.